2019
DOI: 10.3389/fmicb.2019.02572
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Glycine Betaine-Dependent Methylotrophic Methanogenesis Pathway: Insights Into Anaerobic Quaternary Amine Methylotrophy

Abstract: Recent studies indicate that environmentally abundant quaternary amines (QAs) are a primary source for methanogenesis, yet the catabolic enzymes are unknown. We hypothesized that the methanogenic archaeon Methanolobus vulcani B1d metabolizes glycine betaine (GB) through a corrinoid-dependent GB:coenzyme M (CoM) methyl transfer pathway. The draft genome sequence of M. vulcani B1d revealed a gene encoding a predicted non-pyrrolysine MttB homolog (MV8460) with high sequence similarity to the GB methyltransferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 76 publications
1
32
0
Order By: Relevance
“…Thus far, characterized members of the MttB superfamily have been shown to methylate either a supplied free corrinoid cofactor or a corrinoid protein ( 1 , 5 , 6 , 7 , 8 , 9 ). Therefore, we hypothesized that MtyB might also be a corrinoid-dependent methyltransferase but with specificity for γ-butyrobetaine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, characterized members of the MttB superfamily have been shown to methylate either a supplied free corrinoid cofactor or a corrinoid protein ( 1 , 5 , 6 , 7 , 8 , 9 ). Therefore, we hypothesized that MtyB might also be a corrinoid-dependent methyltransferase but with specificity for γ-butyrobetaine.…”
Section: Resultsmentioning
confidence: 99%
“…Phylogenetic analysis indicates substantial diversity among the many MttB superfamily members encoded in the genome of E. limosum ( Fig. S7 ), which led us to investigate their functional diversity ( 5 , 6 , 7 ). Here, we have shown that even two closely related nonpyrrolysine MttB homologs in the E. limosum genome have modified functionality in such a way as to allow their specialization for use with two distinct but related substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to the three-component methyltransferase systems for monomethylamine (MtmBCA), dimethylamine (MtbBCA) and trimethylamine (MttBCA) it has been described for M. barkeri that RamA, a 60-kDa monomeric ironsulfur protein, is required for ATP-dependent reductive activation of methylamine:CoM methyl transfer from all three methylamines (Ferguson et al 2009 ). For the betaine consuming methanogen Methanolobus vulcani B1d it has been shown that the organism possesses the methyltransferase MtgB (FKV42_RS08545) that catalyzes betaine-dependent methylation of free cob(I)alamin (Creighbaum et al 2019 ). Further, proteomic analysis revealed that MtgB, a corrinoid binding protein (FKV42_RS08550), a corrinoid reductive activation enzyme (FKV42_RS10455) and a methylcorrinoid:CoM methyltransferase (FKV42_RS10480) were highly abundant when M. vulcani B1d was grown on betaine relative to growth on trimethylamine.…”
Section: Hydrogenotrophic Methanogenesis With Additional Electron Donmentioning
confidence: 99%
“…Similarly, an MtgB ortholog from Methanolobus sp. B1d was determined to transfer the GBT methyl group to coenzyme M, thereby playing a key role in GBT-dependent methylotrophic methanogenesis ( 25 ).…”
Section: Introductionmentioning
confidence: 99%